ANALISI PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA JASA AKOMODASI DI DESA TETEBATU - Laili, Jamilatul; Ilhamuddin, M.; Adi Permadi, Lalu (Jurnal Magister Manajemen, 2023)
The impact of service quality and cost on customers’ opinions of lodging establishments in Tetebatu Village is the topic of this research. The goal of this research was to determine if there was a correlation between the price and quality of lodgings in Tetebatu Village. Research was conducted in Tetebatu Village with a sample size of 100 people who had stayed in Tetebatu Village lodgings or had at least visited them. Multiple regression analysis was then used to examine the data. Method for analyzing data in SPSS 26. According to the findings of this research, there is a positive and statistically significant relationship between service quality and customer satisfaction 0.000 <0.05 and between pricing and customer satisfaction 0.000 <0.05.